Malaria control and treatment: the role of indigenous practices in Zimbabwe - Zakio Makuvara; Solomon Ramagoai Magano; Grace Mugumbate (Taylor & Francis Group, 2024)
AbstractBeside the use of conventional medicines, Zimbabweans rely on native malaria control and treatment practices. This mini-review therefore seeks to identify and assess applicability of Zimbabwean indigenous practices in the fight against malaria. This work is based on evaluation of literature and data was retrieved from databases such as the Web of Science, Google Scholar, Scopus, PubMed and Research Gate. Five categories of indigenous practices used in the fight against malaria were identified and these are (1) use of herbal and other traditional medicines in malaria, (2) use of traditional environmental indicators, (3) the use of red-hot granite rock and water, (4) burning of dung and plants to deter malaria vectors and (5) spiritual malaria treatment based on faith and traditional healers. Beyond these traditional practices, an overview of medical pluralism, indigenous health practices and decolonisation of public health is presented. It has been shown that herbal medicines are applicable in the fight against malaria. However, burning of plants and dung can be applied in the production of mosquito coils to prevent mosquito bites. Additionally, steaming is just limited to the management of fever and spirituality has no scientific basis on malaria management. Despite the application of indigenous practices in the fight against malaria in Zimbabwe, there is inconclusive evidence on their applicability in the main stream health systems. A comprehensive study should be conducted in order to scientifically evaluate the applicability of these indigenous practices.